(untitled) (Journal of the College of Basic Education, 2025)
Moral Awareness determines whether people are able to discover the moral content of other people’s behavior, determine what Is unethical, and be a necessary part of overall moral behavior. Current research has sought to identify moral Awareness and differences between students in social and work status. The study sample was 100 undergraduate students. An aural awareness scale was adopted and the psychometric properties of the scale were calculated. After analyzing the data statistically, it was found that undergraduate students there was have Moral Awareness University Research recommends raising the level of ethical awareness of university students using Instructions